A new class of potential antidiabetic acetohydrazides: Synthesis, in vivo antidiabetic activity and molecular docking studies (Bangladesh Journal of Pharmacology, 2017)
Two new pharmacologically active series of tetrazolopyridine-acetohydrazide conjugates [9 (a-n), 10 (a-n)] were synthesized by reacting a variety of suitably substituted benzaldehydes and isomeric 2-(5-(pyridin-3/4-yl)-2H-tetrazol-2-yl)acetohydrazides (7, 8). The synthesized compounds were analyzed through FTIR, 1H NMR, 13C NMR and elemental techniques. These acetohydrazides were screened for their in vivo antidiabetic activity and molecular docking studies. An excellent agreement was obtained as the best docked poses show-ed important binding features mostly based on interactions due to an oxygen atom and aromatic moieties of the series. The compounds 9a, 9c and 10l were found to be the most active in lowering blood glucose, having the potential of being good antidiabetic agents.Video Clip of Methodology:Synthesis of 3/4-(2H-tetrazole-5-yl)pyridine: 1 min 57 sec   Full Screen   Alternate